Darriwilian (Middle Ordovician) new trilobites from the Upper Yangtze Region, South China, and their macroevolutionary and paleobiogeographic implications. (March 2022) - Wei, Xin; Zhou, Zhi-Qiang; Zhan, Ren-Bin; Wu, Rong-Chang; Gong, Fang-Yi; Liu, Jian-Bo
Abstract: Two new genera and six new species of trilobites are systematically documented herein: Sinagnostus mirabilis new genus new species, Yanpingia punctata n. gen. n. sp., Illaenus taoyuanensis n. sp., Panderia striolatus n. sp., Nileus yichongqiaoensis n. sp., and Paratiresias peculiaris n. sp. The materials were collected from the Darriwilian (late Middle Ordovician) strata in the Upper Yangtze Region, South China. Also provided is an emended diagnosis of the genus Paratiresias based on the new species Paratiresias peculiaris, which is the oldest known species of this genus with an extremely narrow (sag. and exsag.) preglabellar field. Those Chinese species previously referred to Nanillaenus are reassigned to Illaenus sensu lato. These trilobites add new data for the Darriwilian trilobite macroevolution and show highly endemic to South China and the faunal exchanges between South China and Tarim, Kazakhstan, Alborz, as well as Sibumasu and North China. UUID: http://zoobank.org/ec3be9be-b003-4367-910d-7a0ac4edc982